THU0246 Psychiatric disorders in rheumatology: Evaluation of a screening protocol in 100 hospitalized patients. (23rd January 2014) - Lumetti, F.; Giuggioli, D.; Manfredi, A.; Ferrari, D.; Tedeschini, E.; Simoni, E.; Rigatelli, M.; Ferri, C.
Abstract : Background: Psychiatric disorders, namely depression (D) and anxiety (A) can frequently occur in course of chronic rheumatic diseases. These comorbidities remain often misdiagnosed and consequently not correctly treated. Objectives: Aims of our study are to evaluate the frequency of D and A in a hospitalized sample of rheumatic patients, and to test the efficacy of a screening by mean of questionnaires to detect D and A. Methods: 100 consecutive patients affected by rheumatic diseases were evaluate using the Italian version of Beck Depression Inventory (BDI) and the Sheehan Patient Rated Anxiety Scale (SPRAS). Furthermore, a clinical psychiatric evaluation was performed by rheumatologist's decision or when questionnaires were positive. Results: Of 100 patients studied 28% were affected by arthritis, 38% by connective tissue disease, 22% by vasculitis, 12% by miscellanea. Mean age was 57.2±11.4 years, 82% were females, 68% were married, 10.4% lived alone, 11.2% were unable to work because of their disease, 29.4% underwent a psychopharmacological therapy at the moment of the hospitalization. BDI score was suggestive for D (>17) in 17/100 (17%), but only in 12/100 (12%) D was confirmed by psychiatris evaluation; in the same way, SPRAS score was suggestive for A (>30) in 21/100 (21%) and the diagnosis was confirmed by the psychiatrist in 16/100 (16%). On the whole, 31 psychiatric visits were performed (18 because of questionnaires, 9 after rheumatologist's prescription + questionnaires, 4 after rheumatologist's prescription only); D and/or A was diagnosed in 22/100 (22%) and an appropriate psychopharmacological therapy was consequently prescribed (78% SSRI + BDZ). Conclusions: Depression and anxiety were frequently detected in our population, with a percentage respectively of 12% and 16%. A screening performed using questionnaires is useful to identify a psychiatric comorbidity in these patients; in fact, in our study it proved to have an higher sensitivity than the only rheumatologic evaluation. Nevertheless, because of the presence of false positive results, a psychiatric visit is always necessary to confirm the diagnosis. Disclosure of Interest: None Declared